Hormone Replacement Therapy in Menopause: A Comprehensive Review - Cyrulik, Michalina; Ramlau , Natalia; Kolenda, Dominika; Fischer, Zuzanna; Podolak, Marcin; Hładki, Michał; Simachi , Michalina; Janiszewska, Michalina; Imbirska, Beata; Prager-Zimny, Marta (Journal of Education, Health and Sport, 2025)
Menopause is a natural, physiological milestone in a woman's life. It is defined by the permanent end of menstruation, which follows the depletion of ovarian follicles and a decline in estrogen and inhibin levels. This hormonal transition can give rise to numerous symptoms, including hot flashes, night sweats, mood swings, sleep disturbances, vaginal dryness, and decreased libido. These symptoms can significantly impair quality of life. Hormone therapy (HT) is the most effective treatment for alleviating vasomotor and genitourinary symptoms, and it offers protective benefits for bone health by reducing the risk of osteoporosis. However, HT is also associated with an increased risk of venous thromboembolism and certain hormone-dependent cancers, such as breast and endometrial cancer. Therefore, careful evaluation is necessary before initiating treatment. Emerging evidence highlights the positive effects of non-hormonal strategies, such as physical activity and diets rich in phytoestrogens. These strategies may serve as alternatives to or complements of HT for managing menopausal symptoms. Ultimately, treatment plans must be tailored to each woman's symptoms, health status, and preferences to optimize therapeutic outcomes and improve quality of life during menopause.